THE EFFECT OF THE HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) ON EMPLOYEE PERFORMANCE THROUGH DIGITAL COMPETENCE - Okti Feronika; Defrizal (International Journal of Multidisciplinary Reseach, 2026)
Digital transformation in hospitals requires not only reliable information systems but also employees who can use them effectively. This study examined the effect of the Hospital Management Information System (SIMRS) on employee performance, with digital competence as an intervening variable among management employees at RSUD Ragab Begawe Caram, Mesuji Regency. A quantitative survey design was applied to the entire population of 58 management employees. Data were collected using a five-point Likert questionnaire and analyzed with SPSS 23 through validity and reliability testing, classical assumption testing, simple and multiple linear regression, t-test, F-test, coefficient of determination, and Sobel mediation test. The instruments were reliable, with Cronbach’s alpha values of 0.860, 0.934, and 0.932. SIMRS significantly affected digital competence (t = 14.770; p < 0.001; R² = 0.796), digital competence significantly affected performance (t = 25.787; p < 0.001; R² = 0.922), and SIMRS significantly affected performance (t = 16.594; p < 0.001; R² = 0.831). The combined model explained 93.7% of performance variance, while the Sobel test confirmed a significant mediation effect (Z = 7.556; p < 0.001). The findings indicate that SIMRS optimization should be accompanied by continuous digital competence development.